Formation of high stability bio-inorganic materials: deoxyribonucleic acid (DNA) encapsulated in inorganic layered doubled hydroxide interlamella - Suyub, Iswan Budy; Hussein, Mohd Zobir; Mohd Yusoff, Khatijah (Universiti Putra Malaysia Press, 2005)
Deoxyribonucleic acid (DNA) from salmon sperm was encapsulated into the inorganic Zn/Al-layered double hydroxides (LDHs) interlamellae for the formation of bio-inorganic nanohybrids materials (BINHs) by self-assembly method. Intercalation of DNA into Zn/Al-layered double hydroxides inorganic interlamellae host was carried out at different Zn/Al ratios, Rs and various concentrations of DNA. The physicochemical properties of the as-synthesized LDH and the resulting nanocomposite were studied using powder xray diffraction (PXRD) analysis. Expansion of basal spacing to about 21.2 Å (for R=3 and [DNA] = 100 mg/ml) and 21.9 Å (for R=1 and [DNA] = 44.4 mg/ml) in the resulting nanomaterials was observed compared to their respective LDHs with nitrate as counter ion with basal spacing of 9.0 Å and 8.9 Å. This confirmed the successful intercalation of DNA into the host-matrix, LDHs and the expansion observed is due to spatial orientation of the DNA in the LDH inorganic interlamellae.